(untitled) (Journal of Production Engineering, 2023)
According to the equations for the conservation of energy in a system involving casting-die and the determination of the solid fraction within a given volume element during a temperature drop of ΔT, the general relationship defining the cooling curve during the solidification phase is established. This relationship is expressed analytically, connecting the parameters of the die and the casting, making it convenient for various stages of the solidification process.